PENGAJARAN KATEKETIK PERSPEKTIF KITAB HUKUM KANONIK 1983 - Yohanes Subani (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2017)
The Chruch Law states that there is a proper and serious duty, especially on the part of pastors of souls, to provide for the catechesis of the christian people so that the faith of the faithful becomes living, explicit and productive through formation in doctrine and the experience of christian living. The main elements of the statement are: catechical instruction or formation, pastors are primarilly responsible for catechetical education and the pupose of catechesis.